2021
DOI: 10.1111/bjd.19829
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of cutaneous lymphoma

Abstract: Linked Article: Dobos et al. Br J Dermatol 2021; 184:1059–1067.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
(23 reference statements)
0
4
0
4
Order By: Relevance
“…Regional differences have been reported, with a 15–17 % higher frequency in Asia and South America as compared to Europe [ 13 ]. The incidence of all cutaneous lymphomas has been reported to be about 0.64–0.87/100 000 per year for the USA [ 14 , 15 , 16 , 17 , 18 , 19 ], and 0.29–0.39/100 000 in Europe [ 20 , 21 , 22 , 23 ]. Current registry data from France, however, show an incidence of 0.96/100 000 for cutaneous lymphomas, which is near the incidence in the USA [ 24 ].…”
Section: Introduction and Epidemiologymentioning
confidence: 99%
“…Regional differences have been reported, with a 15–17 % higher frequency in Asia and South America as compared to Europe [ 13 ]. The incidence of all cutaneous lymphomas has been reported to be about 0.64–0.87/100 000 per year for the USA [ 14 , 15 , 16 , 17 , 18 , 19 ], and 0.29–0.39/100 000 in Europe [ 20 , 21 , 22 , 23 ]. Current registry data from France, however, show an incidence of 0.96/100 000 for cutaneous lymphomas, which is near the incidence in the USA [ 24 ].…”
Section: Introduction and Epidemiologymentioning
confidence: 99%
“…In 2018 in France a PCL incidence of 0.96/100 000 was found. 3 A study on Dutch population reported an incidence of Mycosis fungoides (MF) in 0.19 and 0.46/100 000 persons in 2000 and 2020, respectively. 4 A recent analysis showed an incidence rate of CTCL of 1.02/100 000.…”
Section: Introductionmentioning
confidence: 99%
“…En otro estudio realizado también en los Estados Unidos, en 2011, se encontró que los LCCT representaron el 71% y los LCCB el 29% 10 . En concordancia con estos trabajos, en un estudio epidemiológico de LCP realizado en los Países Bajos en 2021 se encuentra una proporción mayor (75%) de LCCT que de LCCB (25%) 11 . Estos resultados contrastan con los de nuestro estudio, ya que si bien coincidimos en el predominio de los LCCT, en nuestra población pudimos observar una frecuencia relativa mayor de LCCT y menor de LCCB, correspondientes al 91.4% y el 8.6%, respectivamente (Tabla 4).…”
Section: Resultsunclassified